2021
DOI: 10.1002/lary.29519
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Injury Following a Diagnosis of Vertigo: A Population‐based Study

Abstract: Background This study aimed to evaluate whether peripheral vestibular disorders (PVD) are associated with subsequent injury. Methods Data for this follow‐up study were retrieved from the Taiwan's National Health Insurance (NHI) Dataset. A total of 251,355 patients with newly diagnosed PVD during January 2015 to December 2016 was identified as the study cohort, the diagnosis date being their index date. Comparison patients were identified by propensity score‐matching (one per case, n = 251,355 controls) from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Our results are in accordance with the findings of previous studies that MD is associated with certain causes of physical injuries, particularly falls 34,36,37 . The higher incidence of falls among patients with MD may be explained by the older age of such patients 21 and the occurrence of MD‐related drop attacks 36,38,39 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are in accordance with the findings of previous studies that MD is associated with certain causes of physical injuries, particularly falls 34,36,37 . The higher incidence of falls among patients with MD may be explained by the older age of such patients 21 and the occurrence of MD‐related drop attacks 36,38,39 .…”
Section: Discussionsupporting
confidence: 92%
“…In 2021, a population‐based study 34 revealed that the risk of various fall‐related injuries was 1.67 times higher in patients with a diagnosed PVD than in controls. Yet, one of the inclusion criteria of this study was a single first‐time diagnosis of a PVD, which may evolve into a more specific form of a vestibular disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most cases of vertigo, about 80%, are caused by local pathology of the ear and vestibular organs [3]. Peripheral vestibular disorders (PVD) affect about 1.2-6.5% of the total population causing considerable economic loss due to missed workdays or early retirement [4], as well as causing personal life disruptions, anxiety, social phobias, traffic accidents, increased risk of injuries [5], and a high risk of reoccurrence of vertigo [6]. Vertigo can be attributed to inner ear pathology, which disrupts the coordinated sensory inputs from the visual, vestibular, and proprioceptive systems responsible for balance and spatial orientation.…”
Section: Introductionmentioning
confidence: 99%